2015
DOI: 10.1002/iub.1408
|View full text |Cite
|
Sign up to set email alerts
|

The circular relationship between matrix metalloproteinase‐9 and inflammation following myocardial infarction

Abstract: Summary Matrix metalloproteinase-9 (MMP-9) regulates remodeling of the left ventricle after myocardial infarction (MI) and is tightly linked to the inflammatory response. The inflammatory response serves to recruit leukocytes as part of the wound healing reaction to the MI injury, and infiltrated leukocytes produce cytokines and chemokines that stimulate MMP-9 production and release. In turn, MMP-9 proteolyzes cytokines and chemokines. While in most cases MMP-9 cleavage of the cytokine or chemokine substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…In the PPI network, IRAK3 and MMP‐9 were found to have interaction with more DEGs, and these two genes also interacted with each other, suggesting that IRAK3 and MMP‐9 might play important roles in MI‐related diseases. Indeed, many studies have shown that MMP‐9 is associated with MI (Deleon‐Pennell, Altara, Yabluchanskiy, Modesti, & Lindsey, ; Iyer, Jung, & Lindsey, ), but there are few studies demonstrating the effects of IRAK3 on MI or the underlying molecular mechanisms. Therefore, the focus of the experiment shifted to the effect IRAK3 had on MI, along with the possible molecular mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In the PPI network, IRAK3 and MMP‐9 were found to have interaction with more DEGs, and these two genes also interacted with each other, suggesting that IRAK3 and MMP‐9 might play important roles in MI‐related diseases. Indeed, many studies have shown that MMP‐9 is associated with MI (Deleon‐Pennell, Altara, Yabluchanskiy, Modesti, & Lindsey, ; Iyer, Jung, & Lindsey, ), but there are few studies demonstrating the effects of IRAK3 on MI or the underlying molecular mechanisms. Therefore, the focus of the experiment shifted to the effect IRAK3 had on MI, along with the possible molecular mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…[44–46] These pleotropic properties also indicate that MMP-9, along with the tissue inhibitor of metalloproteinase-1, which helps regulate the activity of MMP-9, operate in complex ways, only some of which are probably related to inflammation. Indeed, the authors of one review wrote, “we still do not fully understand the complexity of MMP-9 mechanisms of action.”[47] In light of these limitations, we are unable to explain why we found that elevated concentrations of MMP-9 were associated with reduced risk of ventriculomegaly.…”
Section: Discussionmentioning
confidence: 96%
“…In asthma pathogenesis, overproduction of NO synthesized by iNOS leads to an imbalance of Th2 cells, which results in acceleration of the asthmatic response, including inflammatory cell infiltration, airway constriction, and a tissue remodeling process (Comer et al, ; Deacon & Knox, ). The level of the COX‐2 protein is elevated by stimulation of toxic materials such as lipopolysaccharide, chemicals, and allergens; COX‐2 is regarded as a crucial protein in the progression of asthma (Deleon‐Pennell, Altara, Yabluchanskiy, Modesti, & Lindsey, ; Rumzhum & Ammit, ). An increased in COX‐2 levels induces elevation of the level of prostaglandins, which aggravates the inflammatory response (Siloşi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The level of the COX-2 protein is elevated by stimulation of toxic materials such as lipopolysaccharide, chemicals, and allergens; COX-2 is regarded as a crucial protein in the progression of asthma (Deleon-Pennell, Altara, Yabluchanskiy, Modesti, & Lindsey, 2015;Rumzhum & Ammit, 2016). An increased in COX-2 levels induces elevation of the level of prostaglandins, which aggravates the inflammatory response (Siloşi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%